2010
DOI: 10.2217/nnm.10.66
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Drug Delivery by Genetically Engineered High-Density Lipoprotein Nanoparticles

Abstract: The genetic fusion of apoA-I with biologically active peptides potentially enables a simple assembly of biocompatible and versatile drug carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 33 publications
2
48
0
Order By: Relevance
“…The carriers used are recombinant, formed by suspending triglycerides with bacterially expressed Apolipoprotein A1 (Apo-A1) followed by heating and sonication [83]. The advent of Apo-A1 fusion proteins delineated two possibilities; the fusion protein could be therapeutic or, since the Apo-A1 sits at the interface, the fusion protein could include a targeting peptide [84]. In one instance, interleukin-11α was selected as a targeting peptide as the receptor is highly expressed in various cancer cell lines [85,86].…”
Section: Lipoproteins As Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The carriers used are recombinant, formed by suspending triglycerides with bacterially expressed Apolipoprotein A1 (Apo-A1) followed by heating and sonication [83]. The advent of Apo-A1 fusion proteins delineated two possibilities; the fusion protein could be therapeutic or, since the Apo-A1 sits at the interface, the fusion protein could include a targeting peptide [84]. In one instance, interleukin-11α was selected as a targeting peptide as the receptor is highly expressed in various cancer cell lines [85,86].…”
Section: Lipoproteins As Carriersmentioning
confidence: 99%
“…These particles showed selective targeting to osteosarcoma masses and the addition of a cytotoxic peptide demonstrated efficacy in vitro . Efficacy was also demonstrated in mice by fusing the cell penetrating TAT peptide from the human immunodeficiency virus to Apo-A1 carrying unmodified doxorubicin in the particle and administering intravenously [84]. The particles release about 40% of the encapsulated doxorubicin within 5 h in normal saline containing 0.1% bovine serum albumin.…”
Section: Lipoproteins As Carriersmentioning
confidence: 99%
“…30 Briefly, the PC-3, SKOV-3, PZ-HPV, and HiO180 were grown according to procedures and culturing conditions provided by the ATCC in their respective media as stated earlier in 75 cm 2 flasks and incubated at 37°C and 5% CO 2.…”
Section: Determination Of Ic 50 Dosesmentioning
confidence: 99%
“…Additionally, lipid core of these particles is suitable for drug loading (Figure a) and most importantly, because of innate receptor‐dependence of HDLs function, it is possible to direct these particles to different tissues and organs through the addition of various ligands on them (Figure a). Also, adding of specific ligands into the complex may result in the efficient and specific transferring of drugs into the cancer cells, thus leading to suppression of tumor growth . On the other hand, by manipulating the content of different lipids and apolipoproteins, it is possible to change the physicochemical properties of synthetic HDLs that can affect the stability of these particles, the amounts of loaded drugs and their therapeutic efficacy …”
Section: High‐density Lipoproteins and Targeted Drug Delivery In Cancermentioning
confidence: 99%
“…Finally, it has been observed that using of HDLs/DXR complex in addition to the sustained release of DXR led to enhanced intracellular DXR delivery into the MDA‐MB‐231 (human breast cancer cells) and NCI‐H460 (human non‐small‐cell lung cancer). However, adding of TAT into the complex resulted in the transferring of DXR from endosome to nucleus that led to more efficiently suppression of tumor growth than HDLs/DXR complex in mice …”
Section: Application Of Hdls In Passive Drug Deliverymentioning
confidence: 99%